Análise do perfil de risco dos participantes da Fundação CAGECE de Previdência Complementar para uma carteira de investimentos com diferentes níveis de risco - Andrade, Patrick Pinheiro Pessoa de (2020)
Pension funds are fundamental mechanisms for the economy of Brazil, acting as generators of savings and financiers of structural projects in the country, thus having a better understanding of the risk propensity of its participants is primordial. This work deals with an analysis of the risk profile of CAGEPREV participants. Thus, a questionnaire was used and a survey was conducted with a sample of active participants from CAGEPREV and from this, the risk profile of the participants was compared and the results found were compared with those in theory. In order to better understand the determinant elements for the participants risk profile, a multinomial logistic regression model was estimated and the influence of the main characteristics that impact this profile, namely income and equity, was verified.